Non–clinical efficacy, safety and stable clinical cell processing of induced pluripotent stem cell‐derived anti–glypican‐3 chimeric antigen receptor‐expressing natural killer/innate lymphoid cells - Ueda, Tatsuki; Kumagai, Ayako; Iriguchi, Shoichi; Yasui, Yutaka; Miyasaka, Tadayo; Nakagoshi, Kengo; Nakane, Kazuki; Saito, Keigo; Takahashi, Mari; Sasaki, Aki; Yoshida, Shinsuke; Takasu, Naoko; et al. (Cancer science, 2020)
The use of allogeneic, pluripotent stem‐cell‐derived immune cells for cancer immunotherapy has been the subject of recent clinical trials. In Japan, investigator‐initiated clinical trials will soon begin for ovarian cancer treatment using human leukocyte antigen (HLA)‐homozygous‐induced pluripotent stem cell (iPSC)‐derived anti–glypican‐3 (GPC3) chimeric antigen receptor (CAR)‐expressing natural killer/innate lymphoid cells (NK/ILC). Using pluripotent stem cells as the source for allogeneic immune cells facilitates stringent quality control of the final product, in terms of efficacy, safety and producibility. In this paper, we describe our methods for the stable, feeder‐free production of CAR‐expressing NK/ILC cells from CAR‐transduced iPSC with clinically relevant scale and materials. The average number of cells that could be differentiated from 1.8‐3.6 × 106 iPSC within 7 weeks was 1.8‐4.0 × 109. These cells showed stable CD45/CD7/CAR expression, effector functions of cytotoxicity and interferon gamma (IFN‐γ) production against GPC3‐expressing tumor cells. When the CAR‐NK/ILC cells were injected into a GPC3‐positive, ovarian‐tumor‐bearing, immunodeficient mouse model, we observed a significant therapeutic effect that prolonged the survival of the animals. When the cells were injected into immunodeficient mice during non–clinical safety tests, no acute systemic toxicity or tumorigenicity of the final product or residual iPSC was observed. In addition, our test results for the CAR‐NK/ILC cells generated with clinical manufacturing standards are encouraging, and these methods should accelerate the development of allogeneic pluripotent stem cell‐based immune cell cancer therapies. This translational study aimed to develop anti–GPC3 CAR‐expressing NK/ILC cells derived from HLA‐homozygous iPSC clone as an effective cell therapy against disseminated ovarian tumors and to assess the clinical cell manufacturing and pre–clinical aspects of the therapy, including safety and efficacy. Those aspects of the therapy clarified in the study provide perspective for the planned clinical trial.